The housing net worth channel and the public finances: Evidence from a European country panel - David Cronin; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2022)
In the growing literature on the importance of household balance sheets to macroeconomic developments, the relationship between housing wealth and fiscal outturns needs consideration given the likely links between housing market developments and particular tax headings. We adopt the housing net worth model for this purpose. Using a panel dataset of 18 European countries over the period 1998 to 2017, we find changes in housing net worth having a significant impact on the primary budget balance, with increases (decreases) in housing net worth causing the budget balance to improve (dis-improve). Further support for the importance of this channel to the public finances arises by differentiating observations based on the amount of revenue raised under particular tax headings.
Keywords: E62; H31; G51; 330; Housing Wealth; House Prices; Government Budget Balance